Socio-behaviour challenges to phase III HIV vaccine trials in Sub-Saharan Africa - Smit, Joalida (Makerere Medical School, 2005)
BACKGROUND: A number of countries in sub-Saharan Africa are preparing for HIV vaccine efficacy trials. Social and behavioural factors related to HIV transmission require examination in each setting where these trials are considered. As part of this, several countries have also recently begun preparatory research investigating relevant social and behavioural issues. There is a need for a review of the literature to help focus such research efforts in Sub-Saharan Africa. OBJECTIVE: To examine key social and behavioural issues that may impact on the conduct of HIV vaccine efficacy trials in sub-Saharan Africa. DESIGN: Literature review METHODS: Major databases (PubMed, PsychInfo, EBSCOhost, and AIDSline) were searched for literature that discussed social and behavioural issues related to HIV vaccine trials. Three areas are highlighted as being particularly significant for HIV vaccine research: (1) willingness to participate in future HIV vaccine efficacy trials, (2) retention of participants in studies, and (3) sexual risk reporting during trials. For each of these topics, major findings from both developed and developing countries are described and avenues for further research are discussed. RESULTS: There are few data from Sub-Saharan Africa regarding willingness to participate in HIV vaccine trials. Data on participant retention rates varies widely, and maintaining large cohorts of individuals within Phase III trials presents an important challenge. In addition, the possible impact of trial participation on sexual disinhibition, and response bias on sexual risk-reporting remain as issues for HIV vaccine trials in African contexts. CONCLUSIONS: Social and behavioural research forms an important part of preparations for HIV vaccine efficacy trials, and there is a clear need for more research of this type in Sub-Saharan Africa. Innovative approaches are required to address issues such as willingness to participate in vaccine research, participant retention during efficacy trials, and the accurate reporting by participants of sexual risk behaviours.